2005
DOI: 10.1007/s00330-005-2812-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose multidetector-row CT angiography of the infra-renal aorta and lower extremity vessels: image quality and diagnostic accuracy in comparison with standard DSA

Abstract: To investigate the possibility of reducing X-ray exposure during multidetector-row spiral computed tomographic (MDCT) angiography and to compare the image quality and diagnostic accuracy of different dosages with digital subtraction angiography (DSA) in the evaluation of the infra-renal aorta and lower extremities vessels. Seventy-five patients, randomly divided into three groups of 25 patients each, were evaluated for atherosclerotic disease with four-row spiral CT angiography (4x2.5 mm) and DSA. MDCT scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 27 publications
(29 reference statements)
0
31
1
Order By: Relevance
“…Minimizing radiation exposure in MDCTU is generally attempted by reducing the number of acquisitions after contrast material administration and using the lowest possible tube current or dose levels without compromising image quality [15][16][17][18][19]. Nawfel et al stated that the effective dose for MDCTU was 1.5 times higher than that for conventional IVU [20].…”
Section: Discussionmentioning
confidence: 98%
“…Minimizing radiation exposure in MDCTU is generally attempted by reducing the number of acquisitions after contrast material administration and using the lowest possible tube current or dose levels without compromising image quality [15][16][17][18][19]. Nawfel et al stated that the effective dose for MDCTU was 1.5 times higher than that for conventional IVU [20].…”
Section: Discussionmentioning
confidence: 98%
“…The major advantage of MR over CT is that no ionising radiation nor iodinated contrast medium are needed. However, efforts have been made recently to reduce the radiation dose delivered during CT that include the mA dose automodulation during acquisition, as used in the present study, low dose protocol (50 mAs), as proposed by Fraioli et al [17], and low kV settings (100 kVp), as suggested by Wintersperger et al [18]. Care should be taken to use the available protocols for dose reduction in routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…The definition given in the questionnaire for this type of examination may appear not specific enough. It should be noted that this type of examination may be replaced in the future by CT angiography [40,41].…”
Section: Discussionmentioning
confidence: 99%